Localization of plastic deformation and fracture in aluminum polycrystals - Zarikovskaya, N.V.; Zuev, L.B. (Проблемы прочности, 2008)
The effect of the grain size as a basic structural parameter on plastic strain macrolocalization has been studied for polycrystalline aluminum. The mathematical form of the above dependence has been verified. The limiting cases have been defined both for small- and coarse-grain ranges. The effect of sample dimension on the macrolocalization period has been considered.